2015
DOI: 10.1177/0956797615572905
|View full text |Cite|
|
Sign up to set email alerts
|

Dual-Hormone Changes Are Related to Bargaining Performance

Abstract: In the present research, we found that endogenous testosterone and cortisol changes were jointly related to bargaining outcomes. In a face-to-face competitive negotiation (Study 1) and a laboratory-based bargaining game (Study 2), testosterone rises were associated with high earnings and high relationship quality, but only if cortisol dropped. If cortisol rose, testosterone rises were associated with low earnings and poor relationship quality. Conflict between financial and social goals was related to the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 36 publications
(52 reference statements)
7
42
2
Order By: Relevance
“…This finding is consistent with the dual-hormone hypothesis: Groups collectively high in testosterone may have a heightened status drive, but this status drive results in optimal decision-making only when coupled with low cortisol, a potential indicator of reduced stress and attenuated behavioral inhibition. Indeed, recent evidence suggests that increased testosterone combined with reduced cortisol may elevate an individual's status by promoting rational decision-making focused on maximizing financial profits (35). Our findings extend this research to the group level and suggest that groups with a propensity for status attainment, but without inhibition, engage in profit-maximizing decision-making strategies.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This finding is consistent with the dual-hormone hypothesis: Groups collectively high in testosterone may have a heightened status drive, but this status drive results in optimal decision-making only when coupled with low cortisol, a potential indicator of reduced stress and attenuated behavioral inhibition. Indeed, recent evidence suggests that increased testosterone combined with reduced cortisol may elevate an individual's status by promoting rational decision-making focused on maximizing financial profits (35). Our findings extend this research to the group level and suggest that groups with a propensity for status attainment, but without inhibition, engage in profit-maximizing decision-making strategies.…”
Section: Resultssupporting
confidence: 72%
“…There is evidence that the combination of elevated testosterone and reduced cortisol produces greater social rapport in interdependent decisionmaking tasks (35). This past finding suggests that groups in the present study with a collective hormonal profile of high testosterone and low cortisol may have experienced greater intragroup cohesion.…”
Section: Resultssupporting
confidence: 48%
“…Testosterone was of particular interest for leadership as this hormone is linked to numerous social outcomes that are related to leadership, including dominance (e.g., Sellers, Mehl, & Josephs, 2007), entrepreneurship (White, Thornhill, & Hampson, 2006), risk-taking (Sapienza, Zingales, & Maestripieri, 2009), and negotiation performance (Mehta, Mor, & Yap, 2015). In terms of its direct effect on leadership, it was found that testosterone is associated with leaders' dominance when the leader also has a high level of cortisol (Mehta & Josephs, 2010), and that the relationship between power and corruption can be dependent on testosterone (especially when the leader has a great deal of power) .…”
Section: Endocrinology and Leadershipmentioning
confidence: 99%
“…Research to date has tested the dual-hormone hypothesis primarily with 'trait' hormone parameters (basal hormone profiles), but two recent studies show that 'state' testosterone and cortisol changes interactively track bargaining outcomes [27 ]. Additional studies should test the dual-hormone hypothesis with measures of dynamic hormone fluctuations.…”
Section: Future Directionsmentioning
confidence: 99%